STUDY ON KNOWLEDGE, PRACTICE OF PREVENTIVE MEASURES AND ITS EFFECTIVENESS ON HEALTH PROMOTION ON DENGUE AMONG THE RESIDENTS OF A VILLAGE IN IPOH, PERAK - Hussain RS; Davinder S; Rahul S; Ahmad H; Aqila MN; Zharif R (Asian Journal of Medicine & Health Sciences, 2019)
Introduction: The incidence of dengue has risen dramatically high over the last few decades worldwide. Some three billion people are at risk of getting infected with dengue. In Malaysia the total number of dengue cases has been rising annually. In Perak, the number of cases for dengue fever and hemorrhagic dengue fever increased from 421 cases per 100000 population in 2012 to 1024 cases per 100000 in 2013 accounting for an increase of 143.2%. This study aimed to assess the knowledge, practice of preventive measures and effectiveness of health promotion related to dengue among residents of a village in Ipoh. Methodology: This cross sectional study was conducted in 2015. Simple random sampling was applied to choose the samples. Results and discussion: Out of a total of 408 respondents, 61.3% and 74% obtained good scores in knowledge and preventive practice measures respectively. The highest misconceptions occurred on behavior aspects of the Aedes mosquitoes (46.6%) and availability of vaccinations for dengue (40.7%) while 65% of respondents allow fogging activities to be conducted at 2pm (noon). Significant associations were shown between types of occupation and knowledge (p=0.017), level of education and practice (p=0.022), previous exposure among family members and practice (p=0.016), and between knowledge and practice (p=0.011). In conclusion, despite having good knowledge about dengue and potential breeding sites of the Aedes mosquito, the number of dengue cases rising could be due to a quarter of population having poor preventive practices.